Estrategias Metodológicas Para El Desarrollo Del Razonamiento Lógico En La Comprensión De La Asignatura Lenguaje De Programación De La Unidad Educativa Anexa A La UTB De La Ciudad De Babahoyo - Borja Zambrano Bayron (2015)
The present investigative study this related with the learnings and the strategy that use the educational ones specifically in the learning process in the students from the Annexed Educational Unit to the UTB of the City of Babahoyo. The topic is presented to investigate focusing the teacher's work the same one that constitutes a guide and a model to continue of the educandos, the adaptations to the strategies utilized and other means that allow to approach topics of logical reasoning in the students. They are exposed the theoretical and empiric records that you/they sustain this investigation work. Didactic pedagogic texts and designs of new methodologies are revised as well as of the strategies that can be used in the development of a class. In this investigation it is framed a series of concepts and theories that led to the analysis of data. With regard to the methodology they were used technical and surveys that once picked up the data you proceeded to carry out a content analysis that allowed the construction of an action plan that should be on later on in march in a certain period lectivo.